Who Doesn't Come Home? Factors Influencing Mortality Among Long-Term Care Residents Transitioning to and From Emergency Departments in Two Canadian Cities. (October 2021) - Tate, Kaitlyn; Reid, R. Colin; McLane, Patrick; Cummings, Garnet E.; Rowe, Brian H.; Estabrooks, Carole A.; Norton, Peter; Lee, Jacques S.; Wagg, Adrian; Robinson, Carole; Cummings, Greta G.
Residents of long-term care (LTC) whose deaths are imminent are likely to trigger a transfer to the emergency department (ED), which may not be appropriate. Using data from an observational study, we employed structural equation modeling to examine relationships among organizational and resident variables and death during transitions between LTC and ED. We identified 524 residents involved in 637 transfers from 38 LTC facilities and 2 EDs. Our model fit the data, (χ 2 = 72.91, df = 56, p = .064), explaining 15% variance in resident death. Sustained shortness of breath (SOB), persistent decreased level of consciousness (LOC) and high triage acuity at ED presentation were direct and significant predictors of death. The estimated model can be used as a framework for future research. Standardized reporting of SOB and changes in LOC, scoring of resident acuity in LTC and timely palliative care consultation for families in the ED, when they are present, warrant further investigation.